Nasal saline irrigation with azelastine-fluticasone nasal spray in moderate-to-severe persistent allergic rhinitis: a randomized controlled trial - Li, Song; Xu, Rui; Yu, Shaoqing; Wang, Min; Fan, Jiangang; Chen, Ming; Gong, Xiaoyang; Gu, Qingjia; Chen, Fenghong; Jin, Ling; Geng, Congli; Yan, Maoxiao; et al. (Frontiers in Allergy, 2025)
BackgroundSymptom control in patients with moderate-to-severe persistent allergic rhinitis (PAR) who remain inadequately controlled on intranasal corticosteroid monotherapy remains challenging, highlighting the urgent need for more effective treatments. This study aimed to determine whether the addition of nasal saline irrigation to a regimen of intranasal corticosteroids and antihistamines can further improve symptoms in patients with moderate-to-severe PAR.MethodsA multicenter, randomized, open-label, controlled trial was conducted, enrolling 248 eligible patients aged 12 years and above from six clinical centers. They were randomized 1:1 into two groups. The experimental group received nasal saline irrigation combined with azelastine-fluticasone (Aze-Flu) nasal spray, and the control group was treated with azelastine nasal spray and fluticasone nasal spray. The primary outcome was the least-squares-mean (LSmean) change in total nasal symptom score (TNSS) from baseline to four weeks, with secondary outcomes including LSmean change in TNSS from baseline to two weeks, subscores, rhinoscopic scores, visual analogue scale (VAS), and rhinoconjunctivitis quality of life questionnaire (RQLQ) scores.ResultsBoth groups exhibited significant reductions in TNSSs from baseline (p < 0.001). In comparison to the control group, the experimental group exhibited greater LSmean changes in TNSS scores following either two or four weeks of treatment (p < 0.001 at both time points). The experimental group presented more favorable changes in rhinoscopy scores, VAS scores, and RQLQ scores. Both groups showed no substantial differences in adverse events, indicating a comparable safety profile.ConclusionNasal saline irrigation combined with Aze-Flu nasal spray provides additional benefits in managing moderate-to-severe PAR, with good safety and tolerability. This combination therapy could be a valuable option in primary care settings.Clinical Trial Registrationhttp://www.medicalresearch.org.cn, identifier (MR-32-23-044661).